Awareness Regarding Tobacco Consumption in Any Form and Its Ill Effects on Health in a Rural Community in Mandya District, Karnataka - Shashikantha SK; Drishya Jagadeesh (Medsci Publications, 2018)
Introduction: Tobacco consumption rate is still high in spite of much being done to discourage many people from taking up that habit. The number of tobacco related deaths is expected to rise to over eight million deaths yearly by 2030. In India 42.4% of men, 14.2% of women and 28.6% of all adults currently use tobacco (smoked and/or smokeless tobacco). Objective: To determine the prevalence of tobacco consumption and awareness about its ill effects in a community. Materials and methods: It was a community based cross sectional study including 200 subjects. The information regarding the to- bacco use in any form among the respondents aged 15 and above was collected. Suitable percentage and proportion expression of the result was given. Results: The overall prevalence of tobacco consumption was found to be 40%. Eighty percent of them were tobacco smokers. Nearly 90 percent of the respondents had some idea about tobacco and its ill effects. Seventy percent of the total respondents felt the need to attend such de-addiction programmes. Conclusion: Awareness regarding ill effects of tobacco consump- tion still needs improvement among the members of the commu- nity studied, as there is ignorance towards ill health of tobacco use.